Mainstreaming agricultural and water policies for social equity and economic efficiency - Shatanawi M.; Naber S.; Shammout M. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
The world population, especially those living in developing countries, is facing two major challenges represented by increasing water scarcity and looming food crises. In order to solve food shortage and secure a high degree of self-sufficiency, many of these countries have considerably expanded irrigated agriculture and this has resulted in over-exploitation and deterioration of water resources. In spite of all investments, the contribution of the agriculture sector to the national economy is declining while food imports are on the increase. In order to solve these problems an integrated approach has to be adopted by mainstreaming water and agricultural policies aimed at social equity and economic efficiency. These policies should also take into account resources conservation and environmental sustainability without compromising the rights of the future generations. Achieving food security with limited water resources is an approach that appears too ambitious but applicable where political will may rely upon strategic planning and scientific support. During the last two decades, scientific and technological advances made it possible to solve many problems in the field of agricultural development. High-tech applications in agriculture e.g. high-tech irrigation systems, soil-less culture, high-yielding varieties, and biotechnology have allowed to increase production by five to ten times. These technologies are becoming feasible with increasing food price and limited water supply. Under these conditions water productivity will be significantly enhanced compared to traditional or protected agriculture.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)